1994
DOI: 10.1007/bf00351786
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variability detected in a single wheat regenerant involves a rare recombination event across a short repeat

Abstract: The mitochondrial genome of the selfed progeny of a plant regenerated from long-term somatic tissue culture displays specific structural rearrangements characterized by the appearance of novel restriction fragments. A mitochondrial DNA library was constructed from this selfed progeny in the SalI site of cosmid pHC79 and the novel fragments were subsequently studied. They were shown to arise from reciprocal recombination events involving DNA sequences present in the parental plant. The regions of recombination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…As in NCS3, a promoter for the rps3-rp!16 operon appears to have been deleted in MDL, but for rp!16, cotranscription with atp9 may allow its expression. Recombination mediated by short direct repeat sequences in the mitochondrial genome has been suggested to play a role in generating heterogeneous molecules in plant mitochondrial genomes (Small et al, 1989;Fauron et al, 1990Fauron et al, , 1995Hartmann et al, 1994). Involvement of repeated sequences in mitochondrial mutations has also been reported in humans (Wallace, 1992).…”
Section: E I E S S D S L R a R N R L L S E S W E R V E G T E A C G A mentioning
confidence: 99%
“…As in NCS3, a promoter for the rps3-rp!16 operon appears to have been deleted in MDL, but for rp!16, cotranscription with atp9 may allow its expression. Recombination mediated by short direct repeat sequences in the mitochondrial genome has been suggested to play a role in generating heterogeneous molecules in plant mitochondrial genomes (Small et al, 1989;Fauron et al, 1990Fauron et al, , 1995Hartmann et al, 1994). Involvement of repeated sequences in mitochondrial mutations has also been reported in humans (Wallace, 1992).…”
Section: E I E S S D S L R a R N R L L S E S W E R V E G T E A C G A mentioning
confidence: 99%
“…Recombination between two 127 bp repeats resulted in a mtDNA deletion and is believed to have caused the reversion of cms-T maize to a fertile state [9]. Variability in the mitochondrial genome of a wheat regenerant is reported to be due to recombination across a 7 bp mtDNA repeat [ 15]. A ten bp repeat in Oenothera is likely the site of circularization which causes the irreversible formation of a 7.5 kb circular molecule [26].…”
Section: Discussionmentioning
confidence: 99%
“…These genes were not present in the explant source variety. Somac1onal variation has been reported for mitochondrial DNA variation in plants regenerated from triticale (Weigel et al, 1995) and wheat (Hartmann et al, 1994). Several research groups have reported changes in wheat gliadin proteins due to somac1onal variation (Cooper et al, 1986;Maddock et al, 1985;Obukhova et al, 1991).…”
Section: Useful Clonal Variation In Cereal Cropsmentioning
confidence: 93%